THE NEED FOR HARMONIOUS INTERPRETATION OF THE CONSTITUTION IN PAKISTAN: ENSURING COHERENCE AND UNITY IN LEGAL FRAMEWORK - Syeda Saima Shabbir; Hamaish Khan; Waqas Ahmad (International Journal of Contemporary Issues in Social Sciences, 2024)
The Constitution of Pakistan, as the supreme law of the land, lays down the framework for governance, fundamental rights, and the division of powers among the state organs. However, given its complex structure and the evolving socio-political landscape, there is an urgent need for harmonious interpretation of its provisions. Harmonious interpretation seeks to ensure that all constitutional provisions are read in coherence with one another, avoiding conflicts and redundancies. This approach not only preserves the integrity and unity of the Constitution but also enhances the functionality of governance and the protection of fundamental rights. By reconciling apparent contradictions and aligning provisions with the overarching objectives of the Constitution, harmonious interpretation promotes a balanced and effective legal system. This paper argues that adopting a harmonious interpretative approach is essential for addressing the current challenges faced by Pakistan’s judiciary and legislative bodies, thereby fostering a more stable and just society.